Effects of fibrin sealer and resorbable gelatin on the repair of osseous defects in rat tibia - Balducci, Eleny Baducci [UNESP]; Viola, Naiana Vianna; Gaspar, Ana Maria Minarelli (FapUNIFESP (SciELO), 2007)
Gelfoam® - a biologically resorbable gelatin sponge - has the function of restricting hemorrhage, providing platelet rupture, and supporting fibrin threads. Beriplast® - a fibrinogen-thrombin compound - is used to adhere tissues, to consolidate sutures and in hemostasis. The objective of this study was to perform a histological analysis of the effects of haemostatic agents on osseous repair. These materials were inserted into surgical sites in young rat right and left tibiae. After the observation periods of 7, 14, 30 and 45 days, according to the bioethic protocol, the animals were killed, the tibiae were removed and fixed in 10% formalin and decalcified in equal parts of formic acid and sodium citrate solutions. After routine processing, the specimens were embedded in paraffin for microtomy. Analysis of the results demonstrated that the haemostatic agents are effective in controlling hemorrhage; they stimulate osteogenesis, featuring a pattern of osseous tissue formation similar to the control pattern, although the amount of osseous trabeculae was superior, especially in the Gelfoam group in the periods of 7 and 14 days; 30 days after surgery, the delay in tissue healing in the control group in relation to the experimental groups started to decrease, and the control and experimental groups exhibited similar tissue repair after 45 days, when all the groups exhibited secondary osseous tissue.
Keywords: Fibrin foam; Fibrin tissue adhesive; Osteogenesis; Rats; Tibia; fibrin glue; gelatin; gelatin sponge; animal; bone; bone development; bone prosthesis; drug effect; drug screening; pathology; rat; tibia; ultrastructure; wound healing; Animals; Bone and Bones; Bone Substitutes; Drug Evaluation, Preclinical; Fibrin Tissue Adhesive; Gelatin; Gelatin Sponge, Absorbable; Wound Healing